Budidaya Berkelanjutan Kangkung Darat dengan Pupuk Organik Diperkaya di Kelurahan Pasir Putih - Nasution, Hasriati; Suryanto; Yusfaneti; Saad, Asmadi (WIDA Publishing, 2024)
Kangkong (water spinach) is a perennial plant consisting of two main types: upland kangkong (upland water spinach, Ipomoea reptans poir) and aquatic water spinach (Ipomoea aquatica). This plant is rich in vitamin A, vitamin C, and beta-carotene, which act as antioxidants to combat free radicals and prevent cholesterol oxidation. To optimize the growth of upland kangkong on Ultisol soil, enriched organic fertilizer containing dolomite lime, natural phosphate rock, and palm oil ash is required. This fertilizer improves soil fertility, adjusts soil pH, and supports microbial activity. This community service aims to enhance the skills of women in the PKK group RT 23, Pasir Putih Village, Jambi City, in cultivating upland kangkong using enriched organic fertilizer. The activity included two stages: delivering material on the benefits of enriched fertilizer and conducting field practice on its application. The team provided materials such as seeds, fertilizer, supporting tools, and educational resources. The results indicated high enthusiasm from the participants, who gained an understanding of proper fertilizer usage and dosage. Post-training, the participants successfully applied the techniques, resulting in healthy kangkong growth with shiny green leaves. These skills are expected to promote sustainable local agriculture.